Analysis of Factors Militating Against Autonomy in Public Universities in Nigeria - Ogunode, Niyi Jacob; Ibrahim, Usman Kudu (International Journal on Integrated Education, 2023)
This paper examined the problems that have militated against university autonomy in Nigeria. Secondary data were used to provide empirical support for the paper. Data were collected from both print materials and online publications. The paper concluded that integration of the federal universities into the Integrated Payroll and Personnel Information System (IPPIS), centralization of the university system, centralization of admission, governing council dominance, poor implementation of the university Autonomy Bill and poor funding model of public universities are the tools used by the Nigerian government to undermine universities autonomy in Nigeria. Based on these challenges, the paper hereby suggested that the federal government should remove all federal universities from the Integrated Payroll and Personnel Information System (IPPIS) platform and implement the University Autonomy Bill Act of 2004.